Responding to Catastrophic Events
XII, 276 p. 9 illus.
Keywords: An introduction to the range of potential disaster scenarios, covering the issues and organizational relationships of importance to the student of consequence management. These include the roles, responsibilities, and coordination requirements of first responders, the Department of Homeland Security, the Department of Defense, and the military.